Smart Machine Fault Detection System Using IOT - Dr S Usha,; Ch Yamini Lakshmi,; D Pavani,; G Bhagya Raj,; K Vasanth Kumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The loss of one phase of a three-phase Induction Motor (IM) is one of the main causes of motor failure due to overheating. Several protection devices protect IM against this fault, but the majority of conventional devices lack a thorough classification of this type of fault. So, this paper introduces a high-efficiency protection scheme to detect and classify in detail 15 types of faults that can occur due to a phase loss of a three-phase IM. These faults are classified according to the defective phase, fault location either from the power source or beyond the relay point, and motor action modes (standstill mode, transient mode, and steady state mode). One of the advantages of the presented protection method is that it is suitable for many motors because the inputs to the proposed scheme are the per-unit values of both RMS line-line voltages and line currents. The proposed scheme has been validated and tested using MATLAB Simulink under normal conditions and different faults for phase loss, during and after disconnecting the motor, and after pushing the restart button. The simulation results show that the proposed scheme behaves with high efficiency and it is able to detect and classify correctly the phase loss faults for three-phase IM within 1.5 cycles (30 ms) of the fault inception. Thus, the proposed scheme can be used as a simple and reliable scheme in the protection system of a 3-phase IM to detect and classify the different types of phase loss faults.
Keywords: IoT-based fault detection; Smart machine monitoring; Predictive maintenance; Machine health monitoring; IoT sensors for fault detection